The Role of Renewable Energy in Driving Global Energy Transformations - Muhammad Imran; Sumaira Bano; Rai Tooba Manzoor (Social Science Review Archives, 2025)
The research thoroughly examined the worldwide movement towards renewable energy and found notable differences in adoption rates and technical improvements across countries. It also highlighted the possibility of a dramatic change in energy paradigms. Using information from the renewable energy map scenario, research suggests that 2050 renewable energy sources may account for as much as two-thirds of the world's primary energy supply, a significant increase above the reference scenario's modest prediction of 24%. Germany and Denmark, in particular, members of the European Union, stand out as leaders in this shift because of their excellent renewable mix and integration of wind energy. Fast progress is being made in Asia, where nations like China and India show yearly growth rates in the solar and wind industries exceeding 30%. The Americas—well represented by the US, Canada, and Brazil—showcase a variety of renewable integration, with each country's contributions differing. Meanwhile, Middle Eastern nations are gradually broadening their energy portfolios, and although Africa shows promise, the shift is hindered by infrastructure issues. The report highlights the clear worldwide trend towards renewable energy sources. Still, it also draws attention to the persistent inequalities shaped by a wide range of geopolitical, technical, and economic factors. The study findings clarify the present situation and future direction of renewable energy adoption. Still, they also emphasize how crucial it is to implement specific regulations, make targeted investments, and form partnerships to hasten this worldwide change.